Catalytic oxidation of aqueous sulfide in the presence of 3, 3′, 5, 5′-tetra-tert-butyl-4, 4′-stilbenequinone. Issue 12 (2nd December 2019) - Hoang, H. Y.; Akhmadullin, R. M.; Akhmadullina, F. Yu.; Zakirov, R. K.; Akhmadullina, A. G.; Dao, M. U.
Abstract: In this work, the quinone based 3, 3′, 5, 5′-tetra-tert-butyl-4, 4′-stilbenequinone was tested as a catalyst in the sulfide oxidation in aqueous medium. On the basis of the obtained experimental results, the catalytic cycle of sulfide oxidation in the presence of stilbenequinone has been established. The research results also point out that a considerable amount of hydrogen peroxide is formed during catalyst regeneration. Application of the catalyst based on stilbenequinone was made to industrial wastewater treatments. According to Fenton reaction, a new catalytic system composed of ferrous iron and stillbenequinone has been developed for the sulfide oxidation.